Compact Printed Diversity Antenna for LTE700/GSM1700/1800/UMTS/Wi-Fi/Bluetooth/LTE2300/2500 Applications for Slim Mobile Handsets - Singh, Hari S.; Pandey, Gaurav K.; Bharti, Pradutt K.; Meshram, Manoj K. (Electromagnetics Academy, 2015)
A planar, printed multiple-input multiple-output (MIMO) antenna for slim mobile handset is presented. The dual-antenna system, comprises two symmetric antenna elements, is printed on a printed circuit board (PCB) of mobile phone. Each antenna element consists of coupled-fed loop antenna. The loop antenna is formed by a quarter wavelength (at 762MHz) meandered loop strip with end terminal short-circuited to the ground plane. A T-shaped protruded ground is deliberately designed to enhance the impedance matching and decoupled the two closely deposed antenna elements (distance between antenna elements are 0.03λ at 762 MHz). The integrity of the T-shaped decoupling structure and coupled-fed loop antenna array covers LTE700 (0.747 GHz–0.787 GHz) and WWAN (1.7GHz–3.04 GHz) based on −6 dB reflection coefficient and achieves isolation between elements well below −10 dB over all the operating bands. The application platform is LTE700, GSM1700, GMS1800, UMTS, Wi-Fi, Bluetooth, LTE2300, and LTE2500 bands for the 2G/3G/4G mobile terminals. The effect of user proximity by considering the actual mobile environment is also studied in the form of total radiated power (TRP), specific absorption rate (SAR), diversity performances, and radiation performances. Finally, a prototype is fabricated and tested with network analyser. The measured results are found in good agreement with simulated ones.
Keywords: Antenna arrays; MIMO systems; Mobile telecommunication systems; Multiple input multiple output antennas